TOPOLOGICAL SCATTERING RESONANCES AT ULTRALOW FREQUENCIES - Gangaraj, S. Ali Hassani; Valagiannopoulos, Constantinos; Monticone, Francesco (PHYSICAL REVIEW RESEARCH, 2020)
At frequencies much lower than the plasma frequency, individual subwavelength plasmonic scatterers are typically far from any scattering resonance, with the exception of some extreme geometries. Contrary to this conventional behavior, in this paper, we theoretically demonstrate that the application of a weak magnetic bias to a portion of the plasmonic scatterer leads to the emergence of scattering resonances that exist, in principle, for an arbitrarily low frequency. We show that this class of plasmonic resonances originates from ultralow-frequency unidirectional and topological surface modes that emerge at internal interfaces. These topological properties endow the scattering resonances with high robustness against geometrical modifications. Our findings may open new uncharted directions towards the design of robust, shape-independent, subwavelength resonant structures with extreme scattering response
Keywords: Type of access: Open Access; ultralow frequencies